1979
DOI: 10.2172/6315662
|View full text |Cite
|
Sign up to set email alerts
|

Uranium hydrogeochemical and stream sediment reconnaissance of the Dillon NTMS Quadrangle, Montana/Idaho, including concentrations of forty-three additional elements

Abstract: The Los Alamos Scientific Laboratory supervised the collection of 1148 water and 1721 sediment samples from 1796 locations in the Dillon quadrangle, Montana/Idaho, for the US Department of Energy's National Uranium Resource Evaluation program.Samples were collected at a nominal density of one per 10 km 2 except in the Boulder batholith area where the density is approximately one sample per 2 km 2 . Surface waters were taken from flowing streams; ground waters were taken from springs and wells.All water samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1980
1980
1992
1992

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Stream-sediment and stream-water geochemical data from the HSSR study (Broxton, 1978(Broxton, , 1979 and from the present study are interpreted on Plate 4a. During the present study, 24 stream-water and 10 stream-sediment anomalies were identified.…”
Section: 5mentioning
confidence: 52%
See 3 more Smart Citations
“…Stream-sediment and stream-water geochemical data from the HSSR study (Broxton, 1978(Broxton, , 1979 and from the present study are interpreted on Plate 4a. During the present study, 24 stream-water and 10 stream-sediment anomalies were identified.…”
Section: 5mentioning
confidence: 52%
“…Uranium occurrence 12 has been noted by Broxton (1978). It is within a series of permeable rhyolite-bearing laharic deposits near the base of Tertiary sediments.…”
Section: Uranium Occurrences Twelve Uranium Occurrences Have Been Exa...mentioning
confidence: 99%
See 2 more Smart Citations
“…Hamilton (Aamodt, 1978b); Elk City (Broxton, 1978); Dillon (Broxton, 1979); and Bozeman (Bolivar, 1979). Airborne radiometric data for the Butte quadrangle also have been published through the DOE by Texas Instruments, Inc. (1979).…”
mentioning
confidence: 99%